Kinetics of filtration drying of biomass - Kashuba, Liubomyr-Andrii; Mosiuk, Mykola; Аtamanyuk, Volodymyr (Lviv Polytechnic Publishing House, 2016)
Usage of fast-growing energy willow as untraditional source of energy has been showed in the article.
Keywords: kinetics; drying; kinetic curves